Adverse reactions in mRCC patients documented in routine practice by German office-based oncologists and uro-oncologists. (June 2017) - Marschner, Norbert; Müller, Lothar; Münch, Axel; Blumenstengel, Klaus; Hutzschenreuter, Ulrich; Busies, Sabine
Background: Signal transduction inhibitors (STIs) have considerably improved treatment of advanced/metastasized renal cell carcinoma (mRCC). Most safety data for these drugs are derived from clinical trials. The purpose of this study was to evaluate which adverse drug reactions are documented during first-line treatments in routine clinical practice. Patients and methods: The ongoing prospective German mRCC clinical registry is recruiting patients in 110 oncology and urology outpatient centers. Data from the first 250 patients who had completed first-line treatment were analyzed regarding adverse drug reactions (ADRs) documented in patients' medical records. Results: Patients were older than in clinical trials and had comorbidities. Patients were treated with the STIs sunitinib (61%), temsirolimus (14%), sorafenib (10%), or bevacizumab combined with interferon (6%). About 520 ADRs were documented, of which 29% resulted in treatment modifications. The most frequently affected organ system was the gastrointestinal system. The most frequently documented ADRs were mucositis/stomatitis (14%), fatigue (14%), diarrhea (12%), and nausea (12%). Conclusions: In routine practice, mRCC first-line treatments using STIs frequently lead to ADRs partly necessitating treatment modifications. The pattern of reported ADRs is similar to that reported in clinical trials, but frequencies of events differ, especially for symptoms of multifactorial origin that are not immediately associated with the treatment. These results indicate that perception and documentation of adverse reactions is different between clinical trials and routine practice, and that reviews of patients' medical records might not be the best method to assess safety in routine practice.